Vilnius Printers’ Ornaments in the Second Half of the Eighteenth Century as a Source of the History of the Books - Kažuro, Ina (Knygotyra, 2020)
This article focuses on the 18th century printers’ ornaments as an important group of sources of the history of the book. Until now, most studies in Lithuanian had focused on the decorations of books from the 16th– 17th centuries as well as contemporary publications. The present study through several perspectives analyzes the ornaments of the institutional printing houses of Vilnius from the second half of the 18th c. The importance of the chosen topic is substantiated not only with the scarcity of studies but also with the issues associated with the attribution of anonymous publications that had been disseminated during the hand-press period. The study’s sources were images of ornaments in the early printed books as well as European printers’ manuals and inventories of Vilnius printing houses from the period of 18th–early 19th c. The first part of the study has found that in the late 18th c., the Vilnius printers had used printers’ flowers (ornamental pieces of type) and six kinds of decorative blocks, which were carved in wood or metal (i.e., headpieces, tailpieces, vignettes, initials, factotums, and decorations of initial letters). Despite the clear function of these blocks, Vilnius printers freely experimented by placing them in unorthodox places within the books. In the second part of this study, based on a comparison of the printers’ ornaments, the ways of interaction between the Vilnius printing houses are disclosed and interpreted: ornament inheritance, division of labor, the renewal of publications in another printing house, and the falsification of publications. Also, the article discusses cases of ornaments migrating and being copied, which complicates the attribution of anonymous publications. Despite the exploratory nature of the study, it reveals new facts from the operations of 18th c. Vilnius printing houses and allows us to perceive some peculiarities of late GDL culture.